Low hepatitis D co-infection among hepatitis B virus surface antigen-positive blood donors in Kenya - Langat, Benard; Kimutai Kutto, Elisha; Andonov, Anton; Borlang, Jamie; Bii Kipngetich, Andison; Osiowy, Carla; Mutai, Alex; Kirwa, Edward; Kimoloi, Sammy; Maritim Songok, Elijah (International Journal Of Community Medicine And Public Health, 2025)
Background: Hepatitis delta virus (HDV) is a highly pathogenic virus, and causes rapid disease progression from fulminant hepatitis (FH) to development of hepatocellular carcinoma (HCC) in patients co-infected with hepatitis B virus (HBV). However, its exact global burden of HBV-HDV co-infections remains largely obscure, particularly in sub-Saharan Africa. The objective of this study was to determine the prevalence of anti-hepatitis delta virus (anti-HDV) in hepatitis B virus surface antigen (HBsAg)-positive blood donors from Kenya. Methods: A total of 239 HBsAg-positive serum samples, obtained from healthy Kenyan blood donors from June 2014 to November 2017 were analyzed in this cross-sectional study. ELISA was done using the International Immunodiagnostics HDV Ab EIA kit, according to the instructions of the manufacturer, for anti-HDV immunoglobulin G (IgG) determination. Results: Of the 239 HBsAg-positive blood donors, 187 (78.24%) were male, and 52 (21.76%) were female. The average age of the study participants was 24.11 years. Serological analysis revealed that 3/239 (1.26%) study participants were HDV seropositive. Conclusions: Our data suggest that HDV infection is rare among blood donors in Kenya, with anti-HDV positivity rates being relatively lower compared to other countries. Nonetheless, ongoing surveillance is essential to track any potential changes in prevalence over time.